Optical switching and networking handbook - Bates, Regis J. (McGraw-Hill telecommunication, 2001)
Bates believes that with each new technology or protocol there are three questions to be asked: What is it? What is it going to do for me? How much is it going to cost me? This market-driven approach provides a succinct analysis of systems and options without the technical gore.